EXPLORING SEMANTIC MAPPING STRATEGY IN STUDENTS' READING COMPREHENSION - Aini, Rafida (Critical Review of English-Arabic World Journal is an open-access journal published by the Language Development Unit, State Islamic University of Kiai Haji Achmad Siddiq, Jember, 2024)
Reading as a receptive skill is important for all students since they can gain information from the text. However, reading is not an easy matter, many students had difficulty in comprehending texts. As a result, teachers and learners must apply effective strategies in teaching and learning English, particularly in reading comprehension. Islamic Junior High School particularly in the eight-grade, had implemented Semantic Mapping strategy and this strategy assisted learners to effectively comprehend the texts. The study used a qualitative research approach and a case study as the research design. The research data collection methods included observation, interviews, and document review. The results Semantic mapping strategy had further enriched their reading comprehension skills. It also enabled them to organize the ideas into meaningful sentence structures. In addition they managed to acquire new words and phrases. They were also admitted that they could complete the reading comprehension questions easily and were able to write correct sentences.